Unmet supportive care needs and symptom burden in Taiwanese cancer survivors who have completed primary treatment. (August 2018) - Lo, Wan-Tzu; Yates, Patsy; Chan, Raymond Javan
Abstract: Purpose: The number of cancer survivors is increasing due to scientific advances. Previous research on unmet care needs of Taiwanese cancer survivors focused on patients with newly or recently diagnosed cancer. Little is known about the needs and symptom experiences of cancer survivors who have completed treatment. Methods: This is a cross-sectional survey study. Patients who were over 20 years old; had completed their first-line treatment for their cancer were recruited into the study. The questionnaire included demographic characteristics, a global item of quality of life, the physical effects subscale of the Cancer Survivors' Survey of Needs (CSSN), and Cancer Survivors' Unmet Needs measure (CaSUN). Results: One hundred and twenty cancer survivors participated in this study. Body changes, loss of strength, weight change, memory and concentration and fatigue were the top five symptom concerns. Nearly half of the Taiwanese survivors reported needs for up-to-date information, understandable information, and an ongoing case manager were not met. On average, survivors reported 7.68 unmet care needs. Male gender, being under 50 years of age, and having a solid tumor were associated with higher levels of unmet needs. Conclusions: This study provides preliminary information about the type and levels of physical symptom concerns and supportive care needs in long-term cancer survivors in Taiwan. Specific groups of cancer survivors whose needs were unmet were identified. The current healthcare system is not sufficiently meeting the needs of cancer survivors and more efforts are required to advance survivorship care and research in Taiwan. Highlights: Body changes, loss of strength, weight change, memory and concertation, and fatigue were the top five symptom concerns reported by Taiwanese cancer survivors. On average, survivors reported 7.68 unmet care needs. Nearly half reported unmet needs for up-to-date and understandable information, and an ongoing case manager. Male gender, <50 years old, and solid tumor were associated with higher levels of unmet needs.